Mesohepatectomy for colorectal liver metastasis. Case report - Visokai, Vladimir; Lipska, Ludmila; Bergmann, Pavel; Levy, Miroslav; Dutka, Juraj (Hepato-gastroenterology, 2005)
A 54-year-old woman was operated for obstructive ileus in 1996. Obstruction was caused by a tumor of the descending colon invading the abdominal wall. Urgent left colectomy with lymphadenectomy was performed. Microscopically six lymphatic nodes were positive. The patient was postoperatively treated with adjuvant chemotherapy. Fifteen months later the patient underwent a resection of central hepatic segments (Couinaud's segment 4,5,8) for metachronous metastasis. At present the patient has no signs of recurrence, she has returned back to her normal life. Despite several unfavorable prognostic factors--obstruction, abdominal wall infiltration, number of positive nodes, short time between primary tumor resection and diagnosis of liver metastasis and centrally located metastasis with satellite lesions, the patient has been surviving for 6 years now.
Keywords: Neoplasm Invasiveness; Liver Neoplasms; Hepatic Veins; nádory jater; Prognosis; Tomography, X-Ray Computed; Middle Aged; lymfatické metastázy; adenokarcinom; hepatektomie; venae hepaticae; Hepatectomy; Lymphatic Metastasis; nádory tračníku; ženské pohlaví; prognóza; Humans; Colonic Neoplasms; invazivní růst nádoru; lidé středního věku; počítačová rentgenová tomografie; Female; Adenocarcinoma; lidé